Phylogeny and systematics of the Trapeziidae Miers, 1886 (Crustacea: Brachyura), with the description of a new family - Castro, Peter; Ng, Peter K.l.; Ahyong, Shane T. (Zootaxa, 2004)
A revision of the family Trapeziidae Miers, 1886, has shown that it consists of three clades, one of which is elevated to family status, Tetraliidae fam. nov., for the genera Tetralia Dana, 1851, and Tetraloides Galil, 1986. The genera Trapezia Latreille, 1828, Calocarcinus Calman, 1909, Hexagonalia Galil, 1986, Philippicarcinus Garth & Kim, 1983, Quadrella Dana, 1851, and Sphenomerides Rathbun, 1897, remain in the Trapeziidae; Domecia Eydoux & Souleyet, 1842, Jonesius Sankarankutty, 1962, Maldivia Borradaile, 1902, Palmyria Galil & Takeda, 1986, and the fossil genus Eomaldivia M ller & Collins, 1991, in Domeciidae Ortmann, 1893. Cladistic analysis shows that Trapeziidae sensu Miers, 1886, consists of three clades that show convergence as a result of similar habits as symbionts of reef corals and other cnidarians. A list of all recognised genera and species in the three families and their primary synonyms is provided. Keys are also included for four families of Brachyura symbiotic with reef corals, and for the genera and species of Domeciidae, Tetraliidae, and Trapeziidae. Some rare colour figures are reproduced. Three name changes have resulted within the Tetraliidae: Cancer glaberrimus Herbst, 1790, for Tetralia fulva Ser ne, 1984, and Cancer mutus Linnaeus, 1758, for Tetralia armata Dana, 1852, and Tetralia vanninii Galil & Clark, 1988. Nomenclatural problems associated with the repeated use of "forma typica" for various species of Trapezia and Tetralia are resolved. To stabilise the nomenclature of a number of well-known species, neotypes are designated for 13 species of Trapeziidae for which type material is not extant: Trapezia cymodoce (Herbst, 1801), and its three synonyms (Trapezia dentifrons Latreille, 1828, Trapezia dentata var. subintegra Dana, 1852, Trapezia cymodoce var. ornatus Chen, 1933); Trapezia bidentata (Forsk l, 1775), and one of its synonyms (Trapezia ferruginea Latreille, 1828); Trapezia digitalis Latreille, 1828, and one of its synonyms (Trapezia nigrofusca Stimpson, 1858); Trapezia septata Dana, 1852, and one of its synonyms (Trapezia reticulata Stimpson, 1858); Trapezia areolata Dana, 1852; Trapezia bella Dana, 1852; and Trapezia speciosa Dana, 1852. Neotypes are also designated for seven species of Tetraliidae: Tetralia glaberrima (Herbst, 1790), and three synonyms (Trapezia integra Latreille, 1828, Trapezia serratifrons Jacquinot, 1846, Tetralia laevissima Stimpson, 1858); Tetralia muta (Linnaeus, 1758), and one of its synonyms (Tetralia armata Dana, 1852); and Tetraloides nigrifrons (Dana, 1852).